Promoting Cultural Tolerance Through Website-Based Multicultural Content of Bengkulu Province for Elementary School Students - Atika Susanti, (ICoLLiTec (International Conference on Literature Linguistics and Teaching), 2025)
This study aims to describe the content and function of a website developed as a digital learning medium to introduce the multicultural heritage of Bengkulu Province to elementary school students. The study employs a qualitative descriptive approach, with data collected through observation, semi-structured interviews, and document analysis. The instruments used include observation sheets, interview guidelines, and documentation notes. Direct observations were conducted on the website's content, while interviews involved the website developers and elementary school teachers as early users. The results indicate that the website presents cultural information from nine regencies and one city in Bengkulu Province. The content includes aspects such as History and Geographical Location, Social and Economic Background, Community Diversity, Cultural Heritage, Traditions and Celebrations, Tourism and Historical Sites, and Local Narratives. Each region is presented interactively through a combination of text, images, videos, and simple quizzes to enhance student engagement and understanding of cultural diversity. The content is considered effective as a learning resource for fostering appreciation of cultural differences and promoting tolerance values in the context of digital-era education. The findings recommend further development of collaborative content and integration with local curriculum in elementary schools.